Vascular Access Surgery for Hemodialysis and Ischemic Monomelic Neuropathy: Presentations of the Patients Clinically, Electrodiagnostic Correlations and its Management - Waseem Rehman, Mohsin Mahmood, Aqeel Ahmad, Yasir Khan, Naeem Ullah, Salman Rasool (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Ischemic monomelic neuropathy is an uncommon condition observed in end stage renal disease or hemodialysis patients undergoing arteriovenous fistula graft surgery. Objective: To assess the clinical electrodiagnostic and management strategies of patients undergoing arteriovenous fistula surgical graft leading to ischemic monomelic neuropathy. Study Design: Retrospective study Place and Duration of Study: Department of Cardiothoracic Surgery, Shaikh Zayed Hospital, Lahore from 1st May 2023 to 31st October 2023. Methodology: One hundred and three patients presented with fore limb weakness after AV fistula graft surgery were enrolled within the age of 45-70 years. The inclusion criteria of the patients were based on medical history of end stage renal disease, hemodialysis, diabetic or no diabetes as well as clinical complaints including clumsiness, pain and limb weakness post brachiocephalic vascular graft surgery. Each patient underwent neurological assessment/examination and the intensity of weakness was recorded with the sensory involvement and loss. The nerve distribution involved was documented through Nerve conduction studies (NCS) of the limb extremity wherein the reduction in the motor amplitudes of the involved nerves was recorded. The sensory amplitudes were observed. The needle EMG (electromyography) of the limb was performed which presented the denervation affects leading to multiple intrinsic muscles supplied by nerves. Radiological examination using Doppler ultrasound studies was conducted presenting the presence of any evidence related to vascular steal phenomenon. Arteriovenous fistula ligation was performed (Vascular ligation) in 95 cases while rest 4 each had banding and angioplasty performed. Results: The mean age of the patients was 56.5±4.3 years with majority of the cases were between the age group of 61-70 years. The higher prevalence of females than males undergoing surgery for arteriovenous fistula was found. The clinical symptoms of the patients included majority of the cases to have pain and edema while numbness and paralysis was observed in the cases upto 84.46% and 86.40% respectively. The management of the cases showed that 95/103 cases underwent AV fistula ligation with ulnar artery repair in few cases whereas other treatment methods which were applied included 3.8% of the patients undergoing banding or ligation. The highest improvement in blood supply and grip strength was observed in the AV fistula ligation cases. Nerve conduction studies (NCSs) showed absent sensory responses from the left median, ulnar and radial nerves. Electromyography (EMG) showed fibrillation potentials and positive sharp waves in the small muscle of the forelimbs, which indicated active denervation in keeping with an acute nerve lesion. Conclusion: The major clinical symptoms include pain, edema, numbness and paralysis. The diagnosis and treatment of the condition requires electrography, radiological assessment followed by AV fistula ligation for the improvement of blood supply. There is higher efficacy of the AV fistula ligation management procedure than banding or angioplasty in IMN cases. Keywords: Vascular access surgery, Hemodialysis, Ishcemic monomelic neuropathy, Electrodiagnostic